Distribution of overwintering mosquitoes (Diptera: Culicidae) in grassy fields in the Republic of Korea, 2007–2008. Issue 6 (25th November 2013) - Shin, E‐Hyun; Lee, Wook‐Gyo; Chang, Kyu‐Sik; Song, Bong‐Gu; Lee, Sang‐Kee; Chei, Young‐Mi; Park, Chan
Abstract Overwintering mosquitoes in a grassy field were surveyed at 13 different localities from December 2007 to February 2008 in the Republic of Korea (ROK). Mosquitoes were collected by putting a white colored tent on the grass, without the base, and heating the inside of the tent. A total of 784 female adults comprising seven species were collected during the study period, including 395 (45.6%) Anopheles pullus, 338 (43.2%) An. sinensis, 21 (2.7%) An. belenrae, 2 (0.3%) An. kleini, 43 (5.5%) Culex tritaeniorhynchus, 20 (2.5%) Cx. inatomii, and 1 (0.3%) Cx. pipiens complex. The mosquitoes showed different overwintering distributions by temperature zone and locality. Predominant species, the malaria vectors An. pullus and An. sinensis, showed different overwintering distributions. Anopheles pullus had a 90.9% collection rate except for Youngju and an average – 0.6°C temperature between December and February. Anopheles pullus showed >50% collection rate in most regions maintained below an average of −1.4°C, and the rate of An. sinensis showed more than 50% collection rate in all regions maintained at an average above −1.1°C. Other species showed regional characteristics; An. belenrae was distributed in the northwest part of the ROK, and An. kleini was collected rarely at one locality in the middle part of ROK. Culex tritaeniorhynchus, a Japanese encephalitis virus vector, was distributed in the southern and costal region and maintained at an above average of −1.0°C. Culex inatomii was collected on the coastal region of the ROK.